UNIT 25A.3 Laser Microdissection–Mediated Isolation and In Vitro Transcriptional Amplification of Plant RNA. Issue 1 (1st October 2015) - Chandran, Divya; Scanlon, Michael J.; Ohtsu, Kazuhiro; Timmermans, Marja C.P.; Schnable, Patrick S.; Wildermuth, Mary C.
Abstract : Laser microdissection of cells allows for isolation of specific cells of interest for downstream analyses including transcriptional profiling. Plant cells present unique challenges for laser microdissection due to their cellulosic cell walls and large vacuoles. Here we present protocols for plant tissue preparation, laser microdissection of select plant cells, and linear amplification of RNA from dissected cells. Linear amplification of RNA from dissected cells allows sufficient RNA for subsequent quantitative analysis by RT‐PCR, microarray, or RNA sequencing. © 2015 by John Wiley & Sons, Inc.